2019
DOI: 10.21203/rs.2.12214/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HIV Pre-Exposure Prophylaxis (PrEP) Knowledge, Familiarity, and Attitudes among Healthcare Professional Students

Abstract: Background The federal government’s plan to End the HIV Epidemic by 2030 includes a primary goal to reduce new HIV infections by 90 percent. One key contributor to this plan is pre-exposure prophylaxis (PrEP), a medication taken by HIV-uninfected individuals to prevent infection. While knowledge and acceptance of PrEP among clinicians is growing, few studies have assessed knowledge and awareness among future healthcare professionals in academic training programs. Given the limited research on PrEP among healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 25 publications
2
2
0
Order By: Relevance
“…In comparison, over half of the pharmacy students in this study identified appropriate regimens for PrEP and PEP (52.3% and 67.1%, respectively). Additionally, a higher percentage of pharmacy students in this study reported that they intended to counsel patients on PrEP or PEP (85% and 81%, respectively), which is consistent with a previous study indicating pharmacy students' high intention to counsel patients about PrEP (Przybyla et al, 2019). Pharmacy students in this study also reported higher levels of confidence regarding counselling patients on PrEP and PEP (48.8% and 29%, respectively).…”
Section: Bhuiyan Et Alsupporting
confidence: 89%
See 3 more Smart Citations
“…In comparison, over half of the pharmacy students in this study identified appropriate regimens for PrEP and PEP (52.3% and 67.1%, respectively). Additionally, a higher percentage of pharmacy students in this study reported that they intended to counsel patients on PrEP or PEP (85% and 81%, respectively), which is consistent with a previous study indicating pharmacy students' high intention to counsel patients about PrEP (Przybyla et al, 2019). Pharmacy students in this study also reported higher levels of confidence regarding counselling patients on PrEP and PEP (48.8% and 29%, respectively).…”
Section: Bhuiyan Et Alsupporting
confidence: 89%
“…(Przybyla et al, 2019). This study also found that familiarity with CDC PrEP guidelines was significantly associated with intent to counsel patients on PrEP (Przybyla et al, 2019). Similarly, a previous study among prescribers showed a positive association between PrEP knowledge and past and future rates of PrEP prescribing as well as future intent to prescribe PrEP (Blumenthal et al, 2015).…”
Section: Knowledgesupporting
confidence: 74%
See 2 more Smart Citations